Perfil do estresse oxidativo em pacientes portadores de Leucemia Mielóide Crônica - Petrola, Maria Juracy Solon (2011)
Chronic myeloid leukemia (CML) is characterized by clonal expansion of hematopoietic progenitor cells, result from the translocation (9:22). The oncogene BCR-ABL, in the Ph chromosome, is transcribed and translated into a fusion protein BCR / ABL. The ABL tyrosine kinase (TK) in the fusion protein is constitutively activated and is needed for the initial leukemogenic event of CML and its activity induces production of reactive oxygen species (ROS). Of particular relevance to CML is the fact that an increase of ROS can have consequences, facilitating genomic instability may contribute to disease progression. The aim of this study was to determine the oxidative status in patients with CML, in attendance at a university hospital (HUWC). This is a cross-sectional study consisted of 30 adult patients of both sexes with clinical and laboratory diagnosis of CML on treatment with inhibitors (TK) 1st and 2nd generation. The concentrations of malondialdehyde (MDA) and nitrite (NO2-) were performed by spectrophotometric method. The activities of enzymes glutathione peroxidase (GSH-Px) and catalase (CAT) were determined in hemolysate by Glutathione Peroxidase Cellular Activity Kit ® Assay (Sigma-Aldrich) and spectrophotometry, respectively. Total glutathione, reduced glutathione (reduced GSH), glutathione (GSSG) were determined by Total Glutathione Activity Kit ® (Assay Designs, Inc) and calculated the ratio GSH / GSSG. For statistical analysis of nonparametric data was used ® and ANOVA test for multiple comparisons Tukey. It was considered the minimum level of significance of 5%. The average concentrations of NO2- and MDA were increased in CML patients compared to control, regardless of disease activity. The antioxidant profile was characterized by decreased CAT and GSH-Px increased also independent of disease activity. The reduced GSH is presented decreased, the GSSH, increased and GSH / GSSG decreased. It was observed that patients using protease inhibitors of TK 2nd generation of oxidative stress parameters were significantly elevated compared to controls. In the analysis of patients on imatinib were not detected significant changes in oxidative status. We conclude that patients with CML are under oxidative stress and impaired antioxidant activity.